Sedimentation and Diffusion of Nanofluids in Rotating Systems of Metal Friction Elements of Brake (Part II) - Janahmadov, A.Kh.; Volchenko N.А.; Javadov, M.Y.; Volchenko, D.A.; Burava, A.S.; Prysyazhniy, A.V.; Zhuravlev, D.Yu. (Herald of Azerbaijan Engineering Academy, 2023)
For a capillary-porous body formed from nanoparticles, the following characteristics are determined: a differential distribution curve of pores and their total volume per unit volume of the body, the number of reduced cylindrical capillaries in a given cross section, and a capillary pressure curve. The latter are consistent with the thermodynamic relations of the displacement of the wetting phase. The regimes of fluid movement are established, when the accompanying forces are: inertia, capillary, gravitational. A mathematical description of diffusion-sedimentary processes in rotating metal friction elements of braking devices is given